Cathodic electrophoretic deposition of magnesium nitrate modified graphene coating as a macro-scale solid lubricant. (April 2019) - Shen, Bin; Hong, Hong; Chen, Sulin; Chen, Xi; Zhang, Zhinan
Abstract: Graphene had been studied as a macro-scale solid lubricant intensively due to its excellent tribological properties. The electrophoretic deposition (EPD) was supposed to be an effective method of fabricating graphene-related materials, but it was not naturally applicable to the inherently uncharged graphene nanosheets. In the present study, we imposed magnesium nitrate as charging additive to graphene nanosheets and successfully deposited macro-scale graphene coatings. The friction test results showed that EPD prepared graphene coating with various surface morphology and microstructure exhibited highly consistent tribological performance, with a stable COF of ∼0.10 and a specific wear rate around and 10 −7 –10 −6 mm 3 /N·m, reduced by 83% and 2–3 orders of magnitude respectively compared with that of the bare Si substrate. Neither the charging additive nor the normal load exhibited influence on the lubricity of the deposited graphene coating. The tribo-film formed within the central area of wear track determined the durability of the lubricity of EPD prepared graphene coating. The graphene self-contact formed by graphene nanosheets mixed in the tribo-film and adhered on the counterpart ball surface resulted in the low-friction and stable sliding process. The graphene nanosheets retained in the tribo-film was the prerequisite for the EPD prepared graphene coating persisting its lubricity. Graphical abstract: Image 1